Risk Factors And Prevention Strategies For Surgical Site Infections In Emergency Abdominal Surgery - Navalyal, Sanjeev R; Hoogar, Prafullachandra; Naganagoudar, Harshagouda; Mankani, Lata K (Journal of Neonatal Surgery, 2025)
Background: Surgical site infections (SSIs) represent a significant burden in emergency abdominal surgery, with incidence rates substantially higher than in elective procedures. This study aimed to determine the incidence of SSIs following emergency abdominal surgery, identify modifiable risk factors, and evaluate the effectiveness of current prevention strategies in our institutional setting. Methods: This prospective observational cohort study was conducted from January 2023 to June 2024 at KAHER's JGMM Medical College, Hubballi. Adult patients (≥18 years) undergoing emergency abdominal surgery within 24 hours of admission were included. Patients were monitored for SSI development using CDC criteria during hospitalization and at follow-up visits (1 week, 2 weeks, and 30 days postoperatively). Demographic data, preoperative parameters, intraoperative details, and postoperative outcomes were recorded. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors. Results: Among 252 patients enrolled, 41 (16.3%) developed SSIs, with 27 (65.9%) being superficial, 11 (26.8%) deep, and 3 (7.3%) organ/space infections. Open surgical approach (OR=4.78, 95% CI: 2.16-10.59, p<0.001), prolonged operative time >120 minutes (OR=3.21, 95% CI: 1.48-6.97, p=0.003), contaminated/dirty wounds (OR=2.87, 95% CI: 1.31-6.28, p=0.008), and preoperative albumin <3.0 g/dL (OR=2.63, 95% CI: 1.22-5.67, p=0.014) were identified as independent risk factors. Escherichia coli was the most commonly isolated pathogen (58.3%), with 76.4% showing resistance to the prophylactic antibiotics administered. The mean length of hospital stay was significantly longer in patients with SSI compared to those without (14.7±3.2 vs. 7.3±1.8 days, p<0.001). Conclusion: The incidence of SSI following emergency abdominal surgery remains high, with identifiable modifiable risk factors. Implementation of targeted prevention strategies addressing surgical technique, operative duration, and preoperative optimization may reduce SSI rates and improve patient outcomes.